Factors Predicting the Health-Related Quality of Life in Premenopausal Women with Breast Cancer after Receiving Chemotherapy - Techapanya, Yotaka; Saneha, Chongjit; Puwarawuttipanit, Wimolrat; Soparattanapaisarn, Nopadol (Nursing Science Journal of Thailand, 2022)
Purpose: This study aimed to study the predictive ability of menopause symptoms, health literacy, physical activity and anemia on health-related quality of life in premenopausal women with breast cancer after receiving chemotherapy. Design: Correlational predictive design. Methods: The study sample included 129 premenopausal women with breast cancer who were completion of chemotherapy at a super-tertiary hospital in Bangkok. Data were collected by using a demographic questionnaire, Menopause Rating Scale, Health Literacy Questionnaire, Short Form International Physical Activity Questionnaire, and Health-related quality of life questionnaire (FACT-B). All data were analyzed by using descriptive statistics and multiple regression analysis. Main findings: It was found that 39.5% of the sample had severe menopause symptoms, 69% high level of health literacy, 40.3% moderate physical activity and 47.3% anemia. A mean score of overall health-related quality of life among the sample was 113.4 (SD = 17.78). Menopause symptoms, health literacy, physical activity and anemia could account for 51 percent of the variances explained in health-related quality of life (adjusted R2 = .51, F = 27.15, p < .05). Only menopause symptoms ( = - .66, p < .01) and health literacy ( = .21, p < .01) could significantly predict the health-related quality of life. Conclusions and recommendations: Nurses should assess menopause symptoms and health literacy, and take care patients with menopause symptoms as well as promote health literacy in order to improve health-related quality of life of this group of patients.